AAO film with double-layer structure and asymmetric pore channels and preparation method of AAO film

Through multiple anodizing and pore reaming treatments, a double-layer structure asymmetric pore AAO film was prepared, which solved the problem of insufficient performance of traditional AAO films, achieved the diversity of pore structure and precise adjustment of parameters, and improved the stability and application potential of the film.

CN119530920APending Publication Date: 2025-02-28CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411562497.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional symmetric cylindrical channel AAO films have insufficient performance in certain specific applications and cannot meet the needs of more advanced applications.

Method used

The preparation method of a double-layer structure asymmetric pore AAO film is adopted, and a double-layer pore with different pore sizes and structural characteristics are formed through multiple anodization and pore expansion treatments.

Benefits of technology

The diversity of the pore structure and precise adjustment of the parameters is achieved, the stability and asymmetry of the membrane are improved, the preparation cost is reduced, and the application potential is shown in the fields of ion transport and electrochemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530920A_ABST
    Figure CN119530920A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of AAO membranes, in particular to a double-layer structure asymmetric pore channel AAO membrane and a preparation method thereof. According to the method, different electrolytes are adopted for three times of anodic oxidation, in the process, firstly, an aluminum sheet is pretreated, then, phosphoric acid is utilized for primary anodic oxidation, and a formed oxidation layer is removed in a mixed solution of chromic acid and phosphoric acid. And then, phosphoric acid is used again for secondary anodic oxidation, chambering treatment continues to be conducted in the phosphoric acid solution, and a first pore channel with the large pore diameter is obtained. And finally, through a third anodic oxidation method carried out in an oxalic acid solution, a second pore channel with a small pore diameter is continuously generated into the aluminum sheet in the first pore channel, and the asymmetric pore channel AAO with the double-layer structure is successfully prepared. The asymmetric pore channel AAO prepared by the method disclosed by the invention is controllable in parameter, high in stability, higher in asymmetric degree and lower in preparation cost, and shows excellent application potential in the fields of ion transmission, electrochemistry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of AAO membranes, and in particular to a double-layer asymmetric pore AAO membrane and a preparation method thereof. Background Art

[0002] Porous anodic aluminum oxide (AAO) is an oxide layer prepared by anodizing aluminum sheets with an electrolyte solution. It is composed of dense hexagonal columnar units, each of which has a nanoscale pore in the middle, namely a nanochannel. During the preparation process, the pore size, pore spacing and pore depth of AAO can be adjusted by controlling the voltage, temperature, electrolyte and oxidation time to prepare the required AAO membranes with various nanochannel structural parameters. Due to its excellent chemical stability and structural diversity, AAO membranes have received a lot of attention and research. Bionic solid-state nanopores have special physical and chemical properties and show considerable application prospects in many fields, such as energy conversion, biosensing, medical testing, etc.

[0003] Traditional AAO usually has symmetrical cylindrical pores, which to some extent hinders its performance in certain specific applications. To meet the needs of more advanced applications, AAO with new structures has been widely studied. In particular, asymmetric pore AAO has attracted much attention due to its unique transmission and filtration properties. This asymmetric structure has pores of different shapes, sizes or chemical compositions, which provides new possibilities for electrochemical performance and material transport. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a double-layer asymmetric pore AAO membrane and a preparation method thereof.

[0005] A method for preparing a double-layer asymmetric pore AAO membrane of the present invention comprises the following steps:

[0006] S1, cleaning, high temperature annealing and electrochemical polishing of the aluminum sheet;

[0007] S2, placing the aluminum sheet treated in step S1 into a phosphoric acid solution for a first anodization;

[0008] S3, removing the porous aluminum oxide layer of the first anodization;

[0009] S4, placing the aluminum sheet treated in step S3 into a phosphoric acid solution for a second anodization;

[0010] S5, performing hole expansion treatment on the aluminum sheet treated in step S4 in a phosphoric acid solution;

[0011] S6, placing the aluminum sheet treated in step S5 into an oxalic acid solution for a third anodization;

[0012] S7, removing the aluminum substrate on the back of the aluminum sheet treated in step S6 to obtain a double-layer asymmetric pore AAO membrane.

[0013] Furthermore, in step S1, the polishing liquid is a mixture of perchloric acid and anhydrous ethanol.

[0014] Furthermore, the specific operation of step S3 is: soaking the aluminum sheet in a mixed solution of phosphoric acid and chromic acid and then washing it.

[0015] Furthermore, in step S3, a mixed solution of 5.0-6.0 wt % phosphoric acid and 1.5-2.0 wt % chromic acid is used for soaking at a temperature of 50-60° C. for 2-4 hours.

[0016] Furthermore, in step S5, the pore expansion liquid is a 0.4-0.5M phosphoric acid solution, and the pore expansion temperature is 30-45°C.

[0017] Furthermore, the phosphoric acid solution for the first anodization and the second anodization is 1-2 wt %.

[0018] Furthermore, in step S6, the electrolyte for the third anodization is a 0.25-0.35 M oxalic acid solution.

[0019] Furthermore, in step S6, the third anodization voltage is 40-60V, and the oxidation time is 3-10h.

[0020] Furthermore, in step S7, the aluminum base is removed by placing in a cupric chloride solution.

[0021] A double-layer asymmetric pore AAO membrane prepared by the above-mentioned preparation method.

[0022] The present invention uses different electrolytes for three anodic oxidations. In this process, the aluminum sheet is first pretreated, and then phosphoric acid is used for the first anodic oxidation, and the formed oxide layer is removed in a mixed solution of chromic acid and phosphoric acid. Then, phosphoric acid is used again for the second anodic oxidation to obtain a first pore with a large pore size. Subsequently, a pore expansion treatment is performed in a phosphoric acid solution to expand the pore size and reduce the thickness of the barrier layer. Finally, through the third anodic oxidation method performed in an oxalic acid solution, a second pore with a small pore size is continuously generated inside the aluminum sheet in the first pore, and an AAO membrane with a double-layer structure and asymmetric pores having desired characteristics is successfully prepared.

[0023] The present invention can accurately adjust the pore depth, pore diameter and pore ratio of the double-layer asymmetric pore AAO membrane by controlling the process parameters of oxidation and pore expansion. The double-layer asymmetric pore AAO membrane prepared by this method has controllable parameters, high stability, greater asymmetry, and lower preparation cost. The AAO prepared by this method shows excellent application potential in the fields of ion transmission and electrochemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a scanning electron micrograph of the front side of the double-layer asymmetric pore AAO membrane prepared in Example 1;

[0025] Figure 2 is a scanning electron micrograph of the back side of the double-layer asymmetric pore AAO membrane prepared in Example 1;

[0026] Figure 3 is a scanning electron micrograph of a cross section of the double-layer asymmetric pore AAO membrane prepared in Example 1;

[0027] Figure 4 is a scanning electron micrograph of different oxide layers of the double-layer asymmetric pore AAO membrane prepared in Example 1;

[0028] Figure 5 is a statistical diagram of the pore diameters of the double-layer asymmetric pore AAO membrane prepared in Example 1;

[0029] Figure 6 This is a contact angle test photograph of the front side of the double-layer asymmetric pore AAO membrane prepared in Example 1;

[0030] Figure 7 This is a contact angle test photograph of the back side of the double-layer asymmetric pore AAO membrane prepared in Example 1;

[0031] Figure 8 is a scanning electron micrograph of the front side of the double-layer asymmetric pore AAO membrane prepared in Example 2;

[0032] Fig. 9 is a scanning electron micrograph of the back side of the double-layer asymmetric pore AAO membrane prepared in Example 2;

[0033] Fig.10 is a scanning electron micrograph of a cross section of the double-layer asymmetric pore AAO membrane prepared in Example 2;

[0034] Fig.11 is a statistical diagram of the pore diameters of the double-layer asymmetric pore AAO membrane prepared in Example 2;

[0035] Fig.12This is a contact angle test photograph of the front side of the double-layer asymmetric pore AAO membrane prepared in Example 2;

[0036] Fig.13 This is a contact angle test photograph of the back side of the double-layer asymmetric pore AAO membrane prepared in Example 2;

[0037] Fig.14 is a scanning electron micrograph of the front side of the double-layer asymmetric pore AAO membrane prepared in Example 3;

[0038] Fig.15 is a scanning electron micrograph of the back side of the double-layer asymmetric pore AAO membrane prepared in Example 3;

[0039] Fig.16 is a scanning electron micrograph of a cross section of the double-layer asymmetric pore AAO membrane prepared in Example 3;

[0040] Fig.17 is a statistical diagram of the front pore diameter of the double-layer asymmetric pore AAO membrane prepared in Example 3;

[0041] Fig.18 This is a contact angle test photograph of the front side of the double-layer asymmetric pore AAO membrane prepared in Example 3;

[0042] Fig.19 This is a contact angle test photograph of the back side of the double-layer asymmetric pore AAO membrane prepared in Example 3. DETAILED DESCRIPTION

[0043] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0044] Example 1

[0045] (1) Cut the aluminum sheet into 4 cm × 5 cm size and soak it in acetone for 8 h.

[0046] (2) Annealing the aluminum sheet after treatment in step (1) at 500° C. for 4 h.

[0047] (3) Pre-treating the aluminum sheet treated in step (2) by using the aluminum sheet as the anode and the carbon rod as the cathode, and using a solution of perchloric acid and anhydrous ethanol in a volume ratio of 1:4 as the polishing electrolyte. Polishing is performed at 55 V and 10° C. for 90 s, and then taken out and washed with deionized water.

[0048] (4) The aluminum sheet treated in step (3) was subjected to the first step of anodization, with the aluminum sheet as the anode, the platinum electrode as the cathode, and a 1wt% phosphoric acid solution as the electrolyte, and oxidized at a voltage of 40V for 10 minutes, and then the voltage was increased after 10 minutes, and the voltage was increased to 195V at 310s, and oxidized at a voltage of 195V for 1 hour, and the oxidation temperature was -2°C. After the end, the aluminum sheet was taken out and washed with deionized water.

[0049] (5) The aluminum sheet treated in step (4) is immersed in a mixed solution of 6.0 wt% phosphoric acid and 1.8 wt% chromic acid to remove the porous aluminum oxide layer formed by the first anodization at a temperature of 60° C. The immersion time is 3 h, and then it is washed with deionized water.

[0050] (6) The aluminum sheet treated in step (5) is subjected to a second anodization, with the aluminum sheet as the anode, the platinum electrode as the cathode, and a 1wt% phosphoric acid solution as the electrolyte. The aluminum sheet is first oxidized at a voltage of 40 V for 10 min, and then the voltage is increased after 10 min to 195 V at 310 seconds, and oxidized at a voltage of 195 V for 1 h, and then the voltage is reduced to 40 V within 310 seconds for oxidation for 10 min, and the oxidation temperature is -2°C.

[0051] (7) Place the aluminum sheet treated in step (6) in a 0.43 M phosphoric acid solution for pore expansion at a temperature of 37° C. for 1 hour.

[0052] (8) The aluminum sheet treated in step (7) is subjected to a third anodization, the electrolyte is a 0.3 M oxalic acid solution, the third anodization voltage is 40 V, the oxidation time is 6 h, and the oxidation temperature is 10° C.

[0053] (9) placing the aluminum sheet treated in step (8) on a sieve so that its back side can contact with the copper chloride solution to remove the aluminum base, thereby obtaining an asymmetric pore AAO membrane having a double-layer structure, and washing the obtained asymmetric pore AAO membrane with deionized water and then naturally air-drying it.

[0054] Figure 1 This is a front scanning electron microscope image of the sample in this embodiment. Figure 2 This is a back-side scanning electron microscope image. It can be seen that the pore size on the front side is significantly different from that on the back side, indicating that the pore sizes of the upper and lower layers are different.

[0055] Figure 3 This is a scanning electron microscope image of the sample cross section of this embodiment, in which the average thickness of the phosphoric acid oxidation layer is 1.21 μm, and the average thickness of the oxalic acid oxidation layer is 11.26 μm, and the two layers have obvious structural differences.

[0056] Figure 4 This is a scanning electron micrograph of the sample cross section, in which the pores of the two-layer structure can be clearly seen, and the pore diameter of the upper pore is larger than that of the lower pore.

[0057] Figure 5 This is a statistical diagram of the pore diameter on the front side of the sample, with an average pore diameter of 276.49 nm.

[0058] Figure 6 and Figure 7 They are the front and back contact angle images of the samples of this embodiment, wherein the average front contact angle is 86.4°, and the average back contact angle is 59.4°.

[0059] Example 2

[0060] (1) Cut the aluminum sheet into 4 cm × 5 cm size and clean it by soaking in acetone.

[0061] (2) Annealing the aluminum sheet after treatment in step (1) at 500° C. for 4 h.

[0062] (3) Pre-treating the aluminum sheet treated in step (2) by using the aluminum sheet as the anode and the carbon rod as the cathode, and using a solution of perchloric acid and anhydrous ethanol in a volume ratio of 1:4 as the polishing electrolyte. Polishing is performed at 55 V and 10° C. for 90 s, and then taken out and washed with deionized water.

[0063] (4) The aluminum sheet treated in step (3) was subjected to the first step of anodization, with the aluminum sheet as the anode, the platinum electrode as the cathode, and a 1wt% phosphoric acid solution as the electrolyte, and oxidized at a voltage of 40V for 10 minutes, and then the voltage was increased after 10 minutes, and the voltage was increased to 195V at 310s, and oxidized at a voltage of 195V for 1 hour, and the oxidation temperature was -2°C. After the end, the aluminum sheet was taken out and washed with deionized water.

[0064] (5) The aluminum sheet treated in step (4) is immersed in a mixed solution of 6.0 wt% phosphoric acid and 1.8 wt% chromic acid to remove the porous aluminum oxide layer formed by the first anodization at a temperature of 60° C. The immersion time is 3 h, and then it is washed with deionized water.

[0065] (6) The aluminum sheet treated in step (5) is subjected to a second anodization, with the aluminum sheet as the anode, the platinum electrode as the cathode, and a 1wt% phosphoric acid solution as the electrolyte. The aluminum sheet is first oxidized at a voltage of 40 V for 10 min, and then the voltage is increased after 10 min to 195 V at 310 seconds, and oxidized at a voltage of 195 V for 1 h, and then the voltage is reduced to 40 V within 310 seconds for oxidation for 10 min, and the oxidation temperature is -2°C.

[0066] (7) Place the aluminum sheet treated in step (6) in a 0.43 M phosphoric acid solution for pore expansion at a temperature of 37° C. for 30 min.

[0067] (8) The aluminum sheet treated in step (7) is subjected to a third anodization, the electrolyte is a 0.3 M oxalic acid solution, the third anodization voltage is 40 V, the oxidation time is 6 h, and the oxidation temperature is 10° C.

[0068] (9) placing the aluminum sheet treated in step (8) on a sieve so that its back side can contact with the copper chloride solution to remove the aluminum base, thereby obtaining an asymmetric pore AAO membrane having a double-layer structure, and washing the obtained asymmetric pore AAO membrane with deionized water and then naturally air-drying it.

[0069] Figure 8 This is a front scanning electron microscope image of the sample in this embodiment. Fig. 9 This is a back-side scanning electron microscope image. It can be seen that the pore size on the front side is significantly different from that on the back side, indicating that the pore sizes of the upper and lower layers are different.

[0070] Fig.10 This is a scanning electron microscope image of the sample cross section of this embodiment, in which the average thickness of the phosphoric acid oxidation layer is 1.87 μm, and the average thickness of the oxalic acid oxidation layer is 4.27 μm, and the two layers have obvious structural differences.

[0071] Fig.11 This is a statistical diagram of the pore diameter on the front side of the sample, with an average pore diameter of 230.86nm.

[0072] Fig.12 and Fig.13 They are the front and back contact angle images of the sample of this embodiment, wherein the average front contact angle is 64.2°, and the average back contact angle is 70.2°.

[0073] Example 3

[0074] (1) Cut the aluminum sheet into 4 cm × 5 cm size and clean it by soaking in acetone.

[0075] (2) Annealing the aluminum sheet after treatment in step (1) at 500° C. for 4 h.

[0076] (3) Pre-treating the aluminum sheet treated in step (2) by using the aluminum sheet as the anode and the carbon rod as the cathode, and using a solution of perchloric acid and anhydrous ethanol in a volume ratio of 1:4 as the polishing electrolyte. Polishing is performed at 55 V and 10° C. for 90 s, and then taken out and washed with deionized water.

[0077] (4) The aluminum sheet treated in step (3) was subjected to the first step of anodization, with the aluminum sheet as the anode, the platinum electrode as the cathode, and a 1wt% phosphoric acid solution as the electrolyte, and oxidized at a voltage of 40V for 10 minutes, and then the voltage was increased after 10 minutes, and the voltage was increased to 195V at 310s, and oxidized at a voltage of 195V for 1 hour, and the oxidation temperature was -2°C. After the end, the aluminum sheet was taken out and washed with deionized water.

[0078] (5) The aluminum sheet treated in step (4) is immersed in a mixed solution of 6.0 wt% phosphoric acid and 1.8 wt% chromic acid to remove the porous aluminum oxide layer formed by the first anodization at a temperature of 60° C. The immersion time is 3 h, and then it is washed with deionized water.

[0079] (6) The aluminum sheet treated in step (5) is subjected to a second anodization, with the aluminum sheet as the anode, the platinum electrode as the cathode, and a 1wt% phosphoric acid solution as the electrolyte. The aluminum sheet is first oxidized at a voltage of 40 V for 10 min, and then the voltage is increased after 10 min to 195 V at 310 seconds, and oxidized at a voltage of 195 V for 6 h, and then the voltage is reduced to 40 V within 310 seconds for oxidation for 10 min, and the oxidation temperature is -2°C.

[0080] (7) Place the aluminum sheet treated in step (6) in a 0.43 M phosphoric acid solution for pore expansion at a temperature of 37° C. for 1 hour.

[0081] (8) The aluminum sheet treated in step (7) is subjected to a third anodization, the electrolyte is a 0.3 M oxalic acid solution, the third anodization voltage is 40 V, the oxidation time is 6 h, and the oxidation temperature is 10° C.

[0082] (9) placing the aluminum sheet treated in step (8) on a sieve so that its back side can contact with the copper chloride solution to remove the aluminum base, thereby obtaining an asymmetric pore AAO membrane having a double-layer structure, and washing the obtained asymmetric pore AAO membrane with deionized water and then naturally air-drying it.

[0083] Fig.14 This is a front scanning electron microscope image of the sample in this embodiment. Fig.15 This is a back-side scanning electron microscope image. It can be seen that the pore size on the front side is significantly different from that on the back side, indicating that the pore sizes of the upper and lower layers are different.

[0084] Fig.16 This is a scanning electron microscope image of the sample cross section of this embodiment, in which the average thickness of the phosphoric acid oxidation layer is 3.90 μm, and the average thickness of the oxalic acid oxidation layer is 10.99 μm, and the two layers have obvious structural differences.

[0085] Fig.17 This is a statistical diagram of the pore diameter on the front side of the sample, with an average pore diameter of 230.86nm.

[0086] Fig.18 and Fig.19 The front and back contact angle images of the samples in this embodiment are shown respectively, wherein the average front contact angle is 61.65° and the average back contact angle is 75.83°. Anything not mentioned above is applicable to the prior art.

[0087] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a double-layer asymmetric pore AAO membrane, characterized in that: The following steps are involved: S1, cleaning, high temperature annealing and electrochemical polishing of the aluminum sheet; S2, placing the aluminum sheet treated in step S1 into a phosphoric acid solution for a first anodization; S3, removing the porous aluminum oxide layer of the first anodization; S4, placing the aluminum sheet treated in step S3 into a phosphoric acid solution for a second anodization; S5, performing hole expansion treatment on the aluminum sheet treated in step S4 in a phosphoric acid solution; S6, placing the aluminum sheet treated in step S5 into an oxalic acid solution for a third anodization; S7, removing the aluminum substrate on the back of the aluminum sheet treated in step S6 to obtain a double-layer asymmetric pore AAO membrane.

2. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 1, characterized in that: In step S1, the polishing liquid is a mixture of perchloric acid and anhydrous ethanol.

3. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 1, characterized in that: The specific operation of step S3 is: placing the aluminum sheet in a mixed solution of phosphoric acid and chromic acid and then soaking it and then washing it.

4. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 3, characterized in that: In step S3, a mixed solution of 5.0-6.0 wt % phosphoric acid and 1.5-2.0 wt % chromic acid is used for soaking at a temperature of 50-60° C. for 2-4 hours.

5. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 1, characterized in that: In step S5, the pore expansion liquid is a 0.4-0.5M phosphoric acid solution, and the pore expansion temperature is 30-45°C.

6. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 1, characterized in that: The phosphoric acid solution for the first anodization and the second anodization is 1-2 wt %.

7. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 1, characterized in that: In step S6, the electrolyte for the third anodization is a 0.25-0.35 M oxalic acid solution.

8. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 1, characterized in that: In step S6, the third anodization voltage is 40-60V, and the oxidation time is 3-10h.

9. The method for preparing a double-layer asymmetric pore AAO membrane according to claim 1, characterized in that: In step S7, the aluminum base is removed by placing in a cupric chloride solution.

10. A double-layer asymmetric pore AAO membrane prepared by the preparation method according to any one of claims 1 to 9.